Low LDL cholesterol in individuals of African descent resulting from frequent nonsense mutations in PCSK9 - Cohen, Jonathan; Pertsemlidis, Alexander; Kotowski, Ingrid K; Graham, Randall; Garcia, Christine Kim; Hobbs, Helen H (Nature genetics, 2005)
The low-density lipoprotein receptor (LDLR) prevents hypercholesterolemia and atherosclerosis by removing low-density lipoprotein (LDL) from circulation. Mutations in the genes encoding either LDLR 1 or its ligand (APOB) 2 cause severe hypercholesterolemia. Missense mutations in PCSK9 , encoding a serine protease in the secretory pathway 3 , also cause hypercholesterolemia 4 . These mutations are probably gain-of-function mutations, as overexpression of PCSK9 in the liver of mice produces hypercholesterolemia 5 , 6 , 7 by reducing LDLR number. To test whether loss-of-function mutations in PCSK9 have the opposite effect, we sequenced the coding region of PCSK9 in 128 subjects (50% African American) with low plasma levels of LDL and found two nonsense mutations (Y142X and C679X). These mutations were common in African Americans (combined frequency, 2%) but rare in European Americans (<0.1%) and were associated with a 40% reduction in plasma levels of LDL cholesterol. These data indicate that common sequence variations have large effects on plasma cholesterol levels in selected populations.